The road to sustainability must bridge three great divides - Aronson, James (2010)
The world's large and rapidly growing human population is exhausting Earth's natural capital at ever-faster rates, and yet appearsmostly oblivious to the fact that these resources are limited. This is dangerous for our well-being and perhaps for our survival, as documented by numerous studies overmany years.Why are we notmoving instead toward sustainable levels of use? We argue here that this disconnection between our knowledge and our actions is largely caused by three "great divides": an ideological divide between economists and ecologists; an economic development divide between the rich and the poor; and an information divide,which obstructs communications between scientists, public opinion, and policymakers. These divides prevent our economies fromresponding effectively to urgent signals of environmental and ecological stress. The restoration of natural capital (RNC) can be an important strategy in bridging all of these divides. RNC projects and programs make explicit the multiple and mutually reinforcing linkages between environmental and economic well-being, while opening up a promising policy road in the search for a sustainable and desirable future for global society. The bridge-building capacity of RNC derives from its double focus: on the ecological restoration of degraded, overexploited natural ecosystems, and on the full socio-economic and ecological interface between people and their environments.